2015
DOI: 10.1002/clen.201400330
|View full text |Cite
|
Sign up to set email alerts
|

p‐Nitrophenol Removal by Bauxite Ore Assisted Ozonation and its Catalytic Potential

Abstract: The catalytic ozonation process (COP) has attracted wide attention in the treatment of recalcitrant organic contaminants because of its high efficiency and easy operation. In this study, the bauxite ore (BO) was used as a heterogeneous catalyst to catalyze ozonation of p-nitrophenol in water. Calcined BO (CBO) assisted COP (CBO-COP) exhibited a higher degradation and mineralization performance for p-nitrophenol in comparison with raw BO assisted COP and single ozonation process (SOP). The CBO-COP was dominated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 41 publications
1
4
0
Order By: Relevance
“…The rate constants obtained here with the CBD catalysts prepared with the MACS (0.59 ± 0.02 min –1 for Au and 0.50 ± 0.01 min –1 for Ag) are higher than those reported with catalysts prepared by traditional chemical methods. For example, a calcined bauxite ore catalyst gave a pseudo-first-order rate constant of 0.194 min –1 , while the mesoporous α-MnO 2 catalyst gave a rate constant of 0.052 min –1 . This is similar to the value of 0.055 min –1 for a TiO 2 catalyst and 0.0043 min –1 for a titanium dioxide–magnetite composite .…”
Section: Resultssupporting
confidence: 56%
“…The rate constants obtained here with the CBD catalysts prepared with the MACS (0.59 ± 0.02 min –1 for Au and 0.50 ± 0.01 min –1 for Ag) are higher than those reported with catalysts prepared by traditional chemical methods. For example, a calcined bauxite ore catalyst gave a pseudo-first-order rate constant of 0.194 min –1 , while the mesoporous α-MnO 2 catalyst gave a rate constant of 0.052 min –1 . This is similar to the value of 0.055 min –1 for a TiO 2 catalyst and 0.0043 min –1 for a titanium dioxide–magnetite composite .…”
Section: Resultssupporting
confidence: 56%
“…Advanced oxidation processes (AOP) are particularly useful technologies to treat nondegradable compounds present in wastewaters in a wide range of initial concentrations (0.001-10 g•L −1 ) [7][8][9], difficult to remove by the conventional biological processes [10][11][12][13][14]. In this context, different AOPs have been studied, such as ozonation [15,16], photo-degradation [17,18] and electrochemical oxidation [19,20]. All these techniques allow to remove completely 4-NP after 0.25-6 h depending on conditions tested.…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, the identification of active sites is key to understanding the reaction mechanism. Phosphate, carbonate and bicarbonate have been employed to identify active sites, due to their high affinity towards Lewis acid sites and capacity to block them [ 76 ]. The activity and efficiency of the catalyst depend on the nature of the active sites, textural properties such as surface area, porosity and mechanical strength.…”
Section: Catalytic Ozonationmentioning
confidence: 99%
“…Regarding aluminum oxides of natural origin, only few studies are found in the literature. Among them, the studies of Qi et al [ 46 , 153 ] and Chen et al [ 76 ] using raw and modified bauxite (mineral mostly composed of alumina) will be described below.…”
Section: Natural Mineral Catalystsmentioning
confidence: 99%
See 1 more Smart Citation